Pengalaman Belajar Mahasiswa Keperawatan dalam Praktik Klinik - Heyni Fitje Kereh; Erna Rochmawati (Journal of Telenursing (JOTING), 2022)
This study aims to identify nursing student learning experiences in clinical practice. The method used is a literature review of relevant articles in the Pubmed, Google Scholar and ScienceDirect databases. The results show that clinical education is important in integrating nursing learning and application. Nurse educators and clinical nurses should strive to create an environment conducive to maximizing clinical learning for nursing students and educational institutions should plan and design activities to support the implementation of clinical practice. In conclusion, there are four aspects of experience, namely psychological aspects, physical aspects, environmental aspects and social aspects. Keywords: Nursing Students, Learning Experience, Clinical Practice